Die Canabae von Carnuntum - eine Modellstudie der Erforschung römischer Lagervorstädte Von der Luftbildprospektion zur siedlungsarchäologischen Synthese - Doneus, Michael (Verlag der Österreichischen Akademie der Wissenschaften, 2013)
Due to decades of systematic work in aerial archaeology a preliminary master plan of the ancient remains of Roman Carnuntum, that remain hidden beneath the ground, could be made. This plan shows archaeological structures that extend over several square kilometers of the densely built-up area, which include the canabae and features related to the water supply. When viewed together with the published research of older excavations, a reassessment of the previous state of research was carried out and a model of the canabae was developed.